2017
DOI: 10.1038/srep45950
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic signature of muscle fibre hyperplasia in response to faba bean intake in grass carp

Abstract: Fish muscle growth is important for the rapidly developing global aquaculture industry, particularly with respect to production and quality. Changes in muscle fibre size are accomplished by altering the balance between protein synthesis and proteolysis. However, our understanding regarding the effects of different protein sources on fish muscle proteins is still limited. Here we report on the proteomic profile of muscle fibre hyperplasia in grass carp fed only with whole faba bean. From the results, a total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 60 publications
(68 reference statements)
1
47
0
Order By: Relevance
“…Though many studies have explored the molecular changes in FBFGs, the mechanism of increased "hardness" in the muscle of this type of grass carp was not fully understood (Yu et al, 2017). It was suggested that fiber density was one of the main reasons for the observed change in muscle texture, which was due to the attenuation of myocyte hyperplasia (Yu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though many studies have explored the molecular changes in FBFGs, the mechanism of increased "hardness" in the muscle of this type of grass carp was not fully understood (Yu et al, 2017). It was suggested that fiber density was one of the main reasons for the observed change in muscle texture, which was due to the attenuation of myocyte hyperplasia (Yu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The samples of fixed muscle were washed in tap water for 12 h, followed by a routine dehydration in a graded series of ethanol (30, 50, 70, 80, 90, 95, and 100% twice). Samples were then equilibrated in xylene and embedded in paraffin based on standard histological techniques previously described (Yu et al, 2017). Afterward, 5-µm sections were cut with a rotary microtome (RM2235, Leica, Germany), mounted on glass slides, and stained with H&E. Histological samples were observed and photographed using an upright microscope (Leica biosystems, Wetzlar, Germany).…”
Section: Hematoxylin and Eosin (Hande) Muscle Stainingmentioning
confidence: 99%
See 1 more Smart Citation
“…(Clauss, Dove & Arnold, 2008;Fazio, 2018). It has been reported that ingestion of faba bean leads to hemolysis, which results in reduced red blood cell count (RBC) and decreased hemoglobin content, and thereby increases the oxygen requirement in grass carp (Yu et al, 2017). Our previous study has found that the FB and FB water extract groups have low RBC and glucose-6-phosphate dehydrogenase (G6PD) activity, which possibly causes hemolysis (Ma et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, the harvest volume of GCBB was over 22,100 tons in Guangdong Province, China ( Zhang et al, 2015 ). GCBB exhibits increased muscle hardness and crispiness as compared to normal grass carp ( Yu et al, 2017 ) due to a 36.7% higher collagen content in muscle ( Liu et al, 2011 ). However, constant consumption of broad bean by the carp causes intestinal mucosal injury resulting from perpetual inflammation ( Zhang, 2015 ), although the underlying mechanism is unclear.…”
Section: Introductionmentioning
confidence: 99%